Investigating organizational communication between top management and academic staff in Malaysian Technical University Network (MTUN) - Sadia, Aysha (2020)
Organizations are there because of their employees and vice versa employees are there because of their organizations. Communication is a basic element which increases harmony among individuals and organizations for achieving goals at the workplace. Communication is a fundamental skill for organizational development, whereby a lack in communication efficiency leads to a dissonance atmosphere. The aim of this study is to explore the issue of organisational communication between heads of departments and academic staff of all four Malaysian Technical University Network (MTUN). Study focuses on identifying the relationship of communication flow among academic staff and heads of departments in MTUN vertical top down and horizontal layout. The researcher used a mixed method approach to collect the relevant data for this study questionnaire and interview, questionnaire for quantitative approach and interview for qualitative purpose. Quantitative analysis determines the level of communication satisfaction among heads of departments and academic staff. While, qualitative analysis works on communication satisfaction from the perspective of the heads of departments. The population of this study consisted of two groups, namely, heads of departments (n=113) and academic staff (n=3596) from all four MTUNs. Heads of departments were intentionally selected using purposeful sampling while academic staff were selected randomly. This research contributes to academic organization to quantify the internal organizational communication styles, communication satisfaction patterns and explains how leadership styles influence communication satisfaction. The findings revealed inefficient communication among heads of departments and academic staff due to moderate levels of communication in daily conversation at the workplace. This study insights of communication culture and how to foster an engaged heads of departments and staff with communicational behaviour. The research highlighted the areas of less satisfied communication areas as well as reasons for less satisfaction. Suggestions for improvements of communication skills among heads of iv departments and academic staff are essential and crucial communication skills for leaders must be improved for long term organizational goals.